Ivory and paper : adventures in and out of time - Hudson, Ray, 1942- (University of Alaska Press, 2018)
13 year old Booker and his new friend Anna, a Unanga girl, use a magic bookmark to travel via books and stop a twenty-first century pirate who is taking artifacts from the Aleutian Islands.